Patterns and potentials of plant species richness in high‐ and low‐maintenance urban grasslands. Issue 1 (16th September 2016) - Rudolph, Martin; Velbert, Frederike; Schwenzfeier, Stefan; Kleinebecker, Till; Klaus, Valentin H.
Abstract: Aims: We investigated urban grasslands to: (1) explore current patterns of plant species richness in high‐maintenance vs low‐maintenance grasslands, (2) investigate environmental drivers of plant species richness and composition, and (3) derive management recommendations and assess the potential for plant species introduction. Location: Cities of Cologne (50°56′ N, 6°57′ E) and Münster (51°57′ N, 7°37′ E), North Rhine‐Westphalia, Germany. Methods: We performed plant inventories and measured soil and above‐ground biomass characteristics in 100 urban grasslands in two cities differing in population size and environmental setting. The data set covered 35 high‐maintenance grasslands, which are cut or mulched up to 14 times a year, and 65 low‐maintenance grasslands with one to two cuts per year or sheep grazing. We used ANCOVA and DCA to assess drivers of vegetation composition and species richness. The floristic potential and options to restore biodiversity were assessed taking into account maintenance intensity and key abiotic variables of the grasslands using thresholds derived from published literature and our own data. Results: High‐maintenance urban grasslands harboured significantly lower plant species richness compared to low‐maintenance grasslands. However, plant species richness of both grassland types turned out to be lower than that of comparable semi‐natural agricultural grasslands. Floristic composition was primarily conditioned by maintenance intensity, but for plant species richness environmental factors such as soil pH, phosphorus availability and city were additionally important. Just eight of the 100 studied urban grasslands were found to be already valuable and species‐rich, whereas the vast majority showed relatively low species richness but a high potential for species introduction. Conclusions: Apparently, most urban grasslands exhibited quite constrained plant species richness, suffering from high‐maintenance intensity but probably also from dispersal and seed limitations. Nevertheless, as the majority of the studied grasslands showed favourable abiotic preconditions for higher plant species richness, restoration techniques using species introduction could be an easy and promising method to support grassland biodiversity in urban areas. Abstract : When investigating urban grasslands, we found plant species richness being primarily conditioned by maintenance intensity, but also by soil pH, phosphorus availability and study city. Just eight of the 100 studied grasslands were found to be already ecologically valuable and species‐rich, whereas the vast majority showed relatively low species richness but a high potential for species introduction.